Memories of glass : [large type] a novel - Dobson, Melanie (Center Point Large Print, 2020)
"1942. As war rips through the heart of Holland, childhood friends Josie van Rees and Eliese Linden partner with a few daring citizens to rescue Eliese's son and hundreds of other Jewish children who await deportation in a converted theater in Amsterdam. But amid their resistance work, Josie and Eliese's dangerous secrets could derail their friendship and their entire mission. When the enemy finds these women, only one will escape. Seventy-five years later, Ava Drake begins to suspect that her great-grandfather William Kingston was not the World War II hero he claimed to be. Her work as director of the prestigious Kingston Family Foundation leads her to Landon West's Ugandan coffee plantation, and Ava and Landon soon discover a connection between their families. As Landon's great-grandmother shares the broken pieces of her story, Ava must confront the greatest loss in her own life-and powerful members of the Kingston family who will do anything to keep the truth buried"--Provided by publisher.